2016
DOI: 10.1016/j.paid.2016.05.196
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Structure of Temperament in Early and Middle Childhood: A Multi-Method Approach

Abstract: Structural work on the nature of child temperament has lagged far behind parallel research with adults. Further, the structure of extant parent-report questionnaires has been examined only at the higher-order level, using small samples of children. This dissertation addresses this important gap in three studies, examining the lower-and higher-order structure of two widely used parent-reports of child temperament (Studies 1 and 2) and an observational battery of temperament (Study 3). The first study examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The 157 items are grouped into 17 scales. However, due to some authors (e.g., Kotelnikova et al, 2016) had shown that the higher‐order structure of temperament in middle childhood did not bear resemblance to the four‐factor structure posited by Simonds and Rothbart (2004), a Principal Component Analysis (PCA) using a varimax (orthogonal) rotation was performed on these 17 scales, with loadings ≥0.40, to obtain a reliable factor structure. The results of the PCA yielded a four‐factor solution with a good matrices indicator (K‐M‐O = 0.76; Bartlett's sphericity x 2 [ df = 136] = 1542.11, p < .001), accounting for 60.1% of the total variance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 157 items are grouped into 17 scales. However, due to some authors (e.g., Kotelnikova et al, 2016) had shown that the higher‐order structure of temperament in middle childhood did not bear resemblance to the four‐factor structure posited by Simonds and Rothbart (2004), a Principal Component Analysis (PCA) using a varimax (orthogonal) rotation was performed on these 17 scales, with loadings ≥0.40, to obtain a reliable factor structure. The results of the PCA yielded a four‐factor solution with a good matrices indicator (K‐M‐O = 0.76; Bartlett's sphericity x 2 [ df = 136] = 1542.11, p < .001), accounting for 60.1% of the total variance.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to some authors (e.g., Kotelnikova et al, 2016) had shown that the higher-order structure of temperament in middle childhood did not bear resemblance to the four-factor structure posited by Simonds and Rothbart (2004), a Principal Component Analysis (PCA) using a varimax (orthogonal) rotation was performed on these 17 scales, with loadings…”
Section: Temperamentmentioning
confidence: 99%